Geodetsko merjenje dolžin v atletiki ( = Geodetic measurement of distances in athletics) - Aleš Marjetič; Klemen Kregar; Dušan Kogoj (Geodetski Vestnik, 2014)
Geodetic measurements are indispensable beyond the borders of surveying technical tasks. In this paper, the usefulness of geodesy in the measurement of sport results is described for throwing events, in accordance with the rules accepted by the IAAF. The article focuses on terrestrial measurements and geometric solutions for the determination of the result of an athlete in the javelin, hammer and discus throw and shot putt. Some effects on measurements within the specified precision of the result are studied. We analyse the influence of ground inclination and gravity on the sport result and the influence of the location of the instrument on the precision of the length of throw.